Changes in young adult substance use during COVID-19 as a function of ACEs, depression, prior substance use and resilience. Issue 1 (1st December 2022) - Romm, Katelyn F.; Patterson, Brooke; Crawford, Natalie D.; Posner, Heather; West, Carly D.; Wedding, DeEnna; Horn, Kimberly; Berg, Carla J.
Abstract: Background: Given the potential for increased substance use during COVID-19, we examined (1) young adults' changes in cigarette, e-cigarette, marijuana, and alcohol use from pre- to during COVID-19; and (2) related risk/protective factors. These findings could inform intervention efforts aimed at curbing increases in substance use during periods of societal stress. Methods: We analyzed Wave 3 (W3; September–December 2019) and Wave 4 (W4; March–May 2020) from the V ape shop A dvertising, P lace characteristics and E ffects S urveillance (VAPES), a 2-year, five-wave longitudinal study of young adults across six metropolitan areas. We examined risk/protective factors (i.e. adverse childhood experiences [ACEs], depressive symptoms, resilience) in relation to changes in past 30-day substance use frequency. Results: In this sample ( N = 1084, M age =24.76, SD = 4.70; 51.8% female; 73.6% White; 12.5% Hispanic), W3/W4 past 30-day use prevalence was: 29.1% cigarettes (19.4% increased/26.4% decreased), 36.5% e-cigarettes (23.2% increased/28.6% decreased), 49.4% marijuana (27.2% increased/21.2% decreased), and 84.8% alcohol (32.9% increased/20.7% decreased). Multivariate regressions indicated that, greater increases were predicted by: for e-cigarettes, greater ACEs; and for alcohol, greater depression. Among those with low resilience, predictors included: for e-cigarettes, greater depression; and for marijuana, greater ACEs. Conclusions: Interventions to reduce substance use during societal stressors should target both risk and protective factors, particularly resilience.